Efektivitas Pelayanan Tenaga Kesehatan Terhadap Peserta BPJS Kesehatan: (Studi Pada Puskesmas Labuhan Haji Kabupaten Lombok Timur) - Agustiarini Agustiarini; Any Suryani Hamzah (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine and discuss the effectiveness of services for BPJS Health participants and the factors that influence the implementation of health services for BPJS health participants. This type of research is empirical legal research with a statutory approach, conceptual approach and sociological approach. The results showed that the Labuhan Haji Health Center had the capacity of health facilities, health administration, health center safety standards that were effective and in accordance with applicable regulations, as well as the factors that influenced the implementation of BPJS services at the Labuhan Haji Health Center consisting of geographical factors, the availability of Labuhan Haji Health Center facilities, and capacity. Health Human Resources. The availability of health services will affect the success of the implementation of BPJS services at the Labuhan Haji Health Center.